2012
DOI: 10.1111/j.1747-0285.2012.01370.x
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Binding Site Conformations of Protein Tyrosine Phosphatase 1B

Abstract: Hundred and two binding sites from 91 Protein Data Bank files for protein tyrosine phosphatase 1B with different ligands have been compared. It was found that they can be divided into five clusters. Additional clusters were formed by the unliganded and oxidized enzyme. The centroids of the clusters can be used as starting points for further studies of enzyme-inhibitor interaction by computer simulations. A special software tool has been created for the investigation of protein tyrosine phosphatase 1B and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Thus, it is important to develop methods to appropriately choose subsets of structures of the same protein for subsequent studies such as molecular dynamics simulations, mapping of binding sites, molecular docking studies and screening of small molecule binders, and so forth. In 2012, Tanchuk et al used RMSD analysis to interrogate 102 structures of the phosphotyrosine PTP1B and identified seven representative structures . PTP1B is known to exist in an open conformation and a closed conformation and these two states lay in two distinct clusters of structures.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to develop methods to appropriately choose subsets of structures of the same protein for subsequent studies such as molecular dynamics simulations, mapping of binding sites, molecular docking studies and screening of small molecule binders, and so forth. In 2012, Tanchuk et al used RMSD analysis to interrogate 102 structures of the phosphotyrosine PTP1B and identified seven representative structures . PTP1B is known to exist in an open conformation and a closed conformation and these two states lay in two distinct clusters of structures.…”
Section: Discussionmentioning
confidence: 99%
“…We have already studied conformations of PTP1B and found that they can be divided into 5 clusters. Each cluster is a group of similar PTP1b conformations in protein-ligand complexes representing a typical way of ligand binding [10]. A cluster centroid is the most typical representative of the cluster that may be used for computer simulations as a representative of its binding type.…”
Section: тестирование новой оценочной функции для молекулярного докинmentioning
confidence: 99%
“…All available X-ray crystal structures of PTP1B have the main difference, which can be attributed to open or closed conformation of WPD-loop [42]. As shown, the structures belonging to these two groups are also different and can be divided into subclasses [43]. To analyze the binding mode of the phosphonate inhibitors in the active site of PTP1B we applied the previously reported approach of dividing all PDB crystal structures into classes based on similarity of the binding profile.…”
Section: калікс[4]арен α-гідроксифосфонові кислоти як потенційні інгіmentioning
confidence: 99%